1997
DOI: 10.1073/pnas.94.20.10850
|View full text |Cite
|
Sign up to set email alerts
|

Two distinct proteolytic processes in the generation of a major histocompatibility complex class I-presented peptide

Abstract: Although cellular proteins degraded by proteasomes are the source of most antigenic peptides presented on major histocompatibility complex class I molecules, it is unknown whether the eight-to nine-residue peptides that fit in the binding groove of class I molecules are directly produced by proteasomes alone in vivo. If the eight-residue peptide SIINFEKL from chicken ovalbumin is extended by one or several residues at its C terminus and microinjected into cells or expressed from a minigene, it is processed and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
243
1
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(256 citation statements)
references
References 42 publications
11
243
1
1
Order By: Relevance
“…In the cytosol, proteasomes generate most correct carboxyl termini of epitopes (39). In contrast, peptidases producing the carboxyl terminus in the secretory pathway have only been indirectly implicated by our results, where a minimal size CMV 9pp89 peptide was naturally produced from a construct similar to sC-Ova (8).…”
Section: Discussionmentioning
confidence: 52%
“…In the cytosol, proteasomes generate most correct carboxyl termini of epitopes (39). In contrast, peptidases producing the carboxyl terminus in the secretory pathway have only been indirectly implicated by our results, where a minimal size CMV 9pp89 peptide was naturally produced from a construct similar to sC-Ova (8).…”
Section: Discussionmentioning
confidence: 52%
“…A prerequisite for the induction of a CTL response is the generation of peptides from their precursor polypeptides. The major cytosolic protease associated with the generation of antigenic peptides -in particular the C-terminal end of the peptides -is the proteasome [2][3][4][5][6]. After protea-somal cleavage the peptides may be trimmed at the Nterminal end by other peptidases in the cytosol [7].…”
Section: Introductionmentioning
confidence: 99%
“…Further, even in studies of cell lines, ER processing of peptide fragments is not invariably observed. Although N-terminal trimming can occur, the ability to process the C-terminal end of peptides is still controversial (13,24).…”
mentioning
confidence: 99%
“…Further, animals with a deletion of proteasome subunits or the proteasome regulator, PA28 show a decrease in class I expression and/or the generation of specific class I epitopes (8 -10). In addition to the proteasome, other proteases have also been implicated in the processing of protein precursors (11)(12)(13)(14)(15)(16). The relative contribution of different proteases to class I Ag processing has not been established.…”
mentioning
confidence: 99%